Data-driven output-feedback fault-tolerant control for unknown dynamic systems with faults changing system dynamics. (July 2016) - Wang, Jun-Sheng; Yang, Guang-Hong
Abstract : Highlights: An output-feedback ADP method is developed to address the optimal control problem for the unknown LTI discrete-time plant with multiple outputs. A model-free output-feedback FTC scheme considering optimal performance is designed. An example of a DC motor control system is used to demonstrate the benefit of the proposed FTC scheme. Abstract: This paper studies the data-driven output-feedback fault-tolerant control (FTC) problem for unknown dynamic systems with faults changing system dynamics. In a framework of active FTC, two basic issues are addressed: the fault detection employing only the measured input–output information; the controller reconfiguration to achieve optimal output-feedback control in the presence of multiple faults. To detect faults and write the system state via the input–output data, an approach to data-driven design of a residual generator with a full-rank transformation matrix is presented. An output-feedback approximate dynamic programming method is developed to solve the optimal control problem under the condition that the unknown linear time-invariant discrete-time plant has multiple outputs. According to the above results and the proposed input–output data-based value function approximation structure of time-varying plants, a model-free output-feedback FTC scheme considering optimal performance is given. Finally, two numerical examples and a practical example of a DC motor control system are used to demonstrate the effectiveness of the proposed methods.